Hip replacement for femur neck fracture in elderly, effects of delayed surgical intervention on morbidity and mortality, a retrospective comparative study - Ahmed Abdul Habib; Shah Fahad; Muhammad Atif; Javeria Saeed; Pervaiz Hashmi; Mujahid Jamil Khattak (Journal of the Pakistan Medical Association, 2021)
Abstract Hip fracture is one of the most common injuries in elderly population. Delay in operating on patients with hip fracture is associated with greater mortality and morbidity. This was a retrospective review of medical charts of patients underwent primary total hip replacement for neck of femur fractures at our tertiary care level 1 trauma. Data was collected from patient’s chart and analyzed for 30-days mortality and morbidity. A total of 96 patients were included in the study. Out of the 36 patients in delayed THR group, mortality within 30 days was observed in 4 (11.1%) patients while none was noted in the early THR group. The difference was found to be statistically significant with a P-value of 0.008. Continuous....